Fatty amines/oxidized multi-walled carbon nanotubes phase change composites with enhanced thermal properties. (June 2021) - Wang, Shuo; Wang, Chengjun; Chen, Tao; Su, Yanning; Zhu, Zhaoqi; Sun, Hanxue; Liang, Weidong; Li, An
Abstract: The development of phase change composites with both high latent heat and better thermal conductivity is of great importance for thermal energy or solar energy storage applications. Here, three kinds of oxidized multi-walled carbon nanotubes (p-MWCNTs, a-MWCNTs and c-MWCNTs) prepared though multiple oxidations with different oxygen contents were used as porous support materials for construction of phase change composites, in which two kinds of fatty amines (FAs), e.g. tetradecylamine (TDA) and octadecylamine (ODA), were employed as organic phase change materials (PCMs). The thermal conductivity of FAs/oxidized-MWCNTs phase change composites increased with the increase of the oxygen content of oxidized-MWCNTs. As a kind of novel phase change composites, FAs/c-MWCNTs have excellent thermal stability and energy storage density (latent heat up to 273.8 kJ kg −1 for ODA/3%c-MWCNTs), which can compete or superior to those conventional organic PCMs-based (paraffin, PEG, etc.) composites. Benefiting from the merits mentioned above, the FAs/c-MWCNTs phase change composites may have great potentials for real energy-saving applications. Graphical abstract: Image 1 Highlights: The oxygen content of oxidized-MWCNTs is as high as 23.13%. Stable composites were fabricated by doping of fatty amines into oxidized-MWCNTs. The phase change composites with high thermal conductivity. The composites have excellent thermal stability and energy storage density.